Pill-millipedes (Glomerida, Diplopoda) in Taiwan - Golovatch, S. I.; Mikhaljova, E. V.; Chang, Hsueh-Wen (Zootaxa, 2010)
The order Glomerida is represented in Taiwan by five species in two genera, two subfamilies and one family. All species, as well as one genus and one subfamily, seem to be endemic to Taiwan. Among the species, Mauriesia splendida sp. nov. belongs in a new genus, Mauriesia gen. nov., which in its turn represents a new subfamily, Mauriesiinae subfam. nov., the latter differing strikingly from the remaining three subfamilies of Glomeridae both in the presence of a caudomedian lobule on the male pygidium and in telopod stoutness and conformation. Four further species belong to the large, basically Asian genus Hyleoglomeris Verhoeff, 1910: H. aurata sp. nov., H. sinuata sp. nov., H. proximata sp. nov. and H. vittata Verhoeff, 1929. A key is provided to all of the species of Glomerida in Taiwan, and their distributions are mapped and discussed.